Recurrent and Hodgkin’s lymphoma-associated multicentric Castleman’s disease in head and neck region - Selvaraj, Vinodh Kumar; Gudipudi, Deleep Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Castleman’s disease (CD) is a rare lymphoproliferative disorder. It can involve single (unicentric CD) or multiple (multicentric CD) lymph nodal regions. It occurs predominantly in mediastinum, and treatment options include surgery, radiotherapy, chemotherapy, and monoclonal antibodies. Methods: Here, we describe two cases of CD which presented with stridor. The first case was a 38-year-old male, a recurrent multicentric CD in retropharyngeal and cervical lymph nodal regions, treated with radiotherapy and rituximab. The second case was a 25-year-old male, a multicentric CD in lower cervical lymph nodal region, treated with steroids and radiotherapy. He subsequently developed Hodgkin’s lymphoma and was treated for the same with chemotherapy and involved-field radiation therapy (IFRT). Results: Post-treatment, both the patients were asymptomatic and progression-free at 15 months and 42 months follow-up, respectively. Conclusions: Combined modality of treatment with radiotherapy and chemotherapy or monoclonal antibodies offers good local control in multicentric CD.